2012
DOI: 10.7763/ijtef.2012.v3.202
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Work Life Balance of Female Nurses in Hospitals - Comparative Study between Government and Private Hospital in Chennai, TN., India

Abstract: Abstract-Career women are challenged by work and family commitment at the end of each day in Government and private hospital. Majority of women are working through-out week and 53% are struggling to achieve work-life balance. Women reported that their life has become a juggling act as they have to shoulder multiple responsibilities at work and home. Both government and private hospital management need to be conscious of this status of female nurses and periodically review their status. They can create supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The role of nurses has expanded into multi-tasking, and nurses are the first ones who are thought of in the health care industry. It is necessary that their needs be addressed because their job content and satisfaction are absolutely important [12]. Sleutel noted that the nursing practice environment was really just one set of related concepts that had been described as "organizational factors that influenced nursing practice" [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of nurses has expanded into multi-tasking, and nurses are the first ones who are thought of in the health care industry. It is necessary that their needs be addressed because their job content and satisfaction are absolutely important [12]. Sleutel noted that the nursing practice environment was really just one set of related concepts that had been described as "organizational factors that influenced nursing practice" [27].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the barriers and looking for possible solutions are important issues to deal with if the current nursing shortages are to be resolved. The role of nurses has expanded and the demands on nurses have increased [11,12], so setting priorities has become a major challenge faced worldwide by health plan decision-makers with limited resources [13]. The magnet hospital concept presents itself as a possible solution to the challenge of nursing shortages [10]; however, previous research has focused primarily on provider and patient correlations with magnet hospital characteristics, and less on the identification of an organizational social structure that would promote its development and maintenance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nathani and Jha (10) explored some of the factors influencing WLB namely, ageing population, emergence of service sector industries, technological advancement of work, skill shortages, and loss of social support network, globalisation and demographic shift of workforce. Lakshmi, Ramachandran and Boohene (11) identified the issues connected with work life balance of female nurses in government and private hospitals in Tamil Nadu, India and the results also indicated that both government and private hospital nurse"s work life balance is a challengeable one. The study suggested that government and private hospital management eed to be conscious of the status of female nurses and periodically review their work and personal life satisfaction.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another Indian study by Lakshmi, et al of Chennai, showed that a majority of nurses are working through-out week and 53% are struggling to achieve work-life balance. [14] They also made comparisons between nurses from the public and private set-up. In a study by Gulavani, et al, at Karad, Maharashtra, a majority of 100 nurses reported there is frequent occurrence of stress associated with Uncertainty by concerning treatment (49%), dealing with patient and families (48%), workload (59%), conflict with doctors (49%), death and dying (50%), conflict with supervisors (52%), where as inadequate emotional preparation (68%), discrimination (48%), conflict with peers (53%) as occasionally stress inducing causes as reported by nurses.…”
Section: Section: Medicinementioning
confidence: 99%